4CPS-268 Evaluation of the satisfaction of the implementation of a pharmaceutical letter of hospital discharge transmitted to patients and community health professionals. (March 2019) - Salgues, J; Viault, L; Cosson, M; Lohan-Descamps, L; Rosant, D; Roch-Torreilles, I; Villiet, M; Goulabchand, R; Fesler, P; Le Quellec, A; Breuker, C
Abstract : Background: The development of the activities of medication conciliation (CM) at admission and discharge have reduced medication errors. Due to the lack of time and adequate tools, CM information is rarely transmitted to patients or community health professionals (CHP). In our hospital, since July 2017, a pharmaceutical letter (PL) of hospital discharge is edited from CM data and integrated into the patient's computerised record. This PL is given and explained to the patient and transmitted to CHP (general practioner (GP), pharmacist, rehabilitation centre). Purpose: The objective of this study was to assess the satisfaction of PL transmission to CHP and patients. Material and methods: We conducted this prospective study in two internal medicine units from July 2017 to February 2017. This study using data regarding two internal medicine units (44 beds) were collected from July 2017 to February 2018. The PL and a satisfaction questionnaire were explained and given to the patient, and sent (email, regular mail or fax) to the pharmacy, the GP and/or the medical centre. The questionnaire included 10 questions, satisfaction scales from 0 (not at all satisfied) to 10 (very satisfied). Results: Two-hundred and six patients were included: sex ratio M/F=0.6, mean age 72 years' old and average length of stay of 13 days. Respectively 112 (54%), 112 (54%), 143 (69%) and 66 (32%) PL were given and explained to patients, sent to pharmacies, doctors and others health centres. The response rates for the questionnaires were respectively 53% (59) for patients, 39% (44) for pharmacies, 5% (seven) for GP and 9% (seven) for others centres. Overall satisfaction was 8.6±2.1 for patients, 9.3±0.9 for pharmacies, 8.2±2.3 for GPs and 8.7±1.7 for other centres. According to the patients, the explanations of PL significantly improved the knowledge of their treatments (7.9±2.3 versus 9.7±0.9, p<0.001). Concerning sending modalities, the satisfactions were respectively 9.3±1.1, 6.7±3.9 and 9±1.3 for pharmacies, GPs and other centres. Satisfaction concerning quality of information were respectively 9.5±0.8, 9.2±1.2, 7.3±2 and 8.5±1.4 for patients, pharmacists, GPs and other centres. Conclusion: According to these results, we observed a very positive overall satisfaction, on the one hand of patients, and on the other, of CHP. References and/or acknowledgements: https://www.ncbi.nlm.nih.gov/pubmed/28007439 No conflict of interest.